Exploring Virtual Reality in Pre-Hajj Training to Deepen Pilgrims' Sense of Spiritual Understanding - Fikria, Averoes; Rafsanjanie, Faiz Hosainie (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2025)
The Manasik Haji program was launched by the Indonesian Ministry of Religious Affairs to improve pilgrims' comprehension of Islamic-law-based Hajj rites. In response to global technological trends, institutions such as Umm Al-Qura University and the Grand Mosque of Saudi Arabia have launched virtual reality (VR) experiences that recreate the Hajj pilgrimage. This study explores how VR-based Pre-Hajj training contributes to ritual comprehension and spiritual immersion. A systematic literature study was conducted, as well as an analysis of articles from mass media that highlighted advancements in virtual Hajj practices. Findings show that, despite ongoing worries about authenticity, virtual reality (VR) holds great promise for assisting pilgrims in visualizing and internalizing ritual sequences, especially for those who have limited access to conventional training. This research contributes to the growing discourse on the intersection of technology and religion, offering new insights into how digital tools can enhance religious practice in a contemporary context.